Pre-hospital Prognostic Factors of 30-Day Survival in Sepsis Patients; a Retrospective Cohort Study - Huabbangyang, Thongpitak; Klaiangthong, Rossakorn; Jaibergban, Fahsai; Wanphen, Chanathip; Faikhao, Thanakorn; Banjongkit, Passakorn; Kuchapan, Ratchaporn (Archives of Academic Emergency Medicine, 2023)
Introduction: According to excising findings, if the emergency management system (EMS) operation will be developed, the survival outcome of sepsis patients might improve. This study aimed to evaluate the pre-hospital associated factors of survival in sepsis patients. Methods: This retrospective cohort study was conducted on patients diagnosed with sepsis, coded with the Thailand emergency medical triage protocol and criteria-based dispatch symptom group 17. Information on the 30-day survival rate of patients was obtained from the electronic medical records. Pre-hospital factors associated with 30-day survival were analyzed using univariate and multivariate logistic regression analyses and were reported using odds ratio (OR) with 95% confidence interval (CI). Results: 300 patients diagnosed with sepsis were enrolled. Among them, 232 (77.3%) survived within 30 days. Non-survived cases had significantly older age (p = 0.019), lower oxygen saturations (92.5% vs. 95.0%; p = 0.003), higher heart rate (p = 0.001), higher respiratory rate (p < 0.001), lower level of consciousness (p < 0.001), higher disease severity based on qSOFA score (p = 0.001), and higher need for invasive airway management (p = 0.001) and supplementary oxygen (p = 0.001). The survival rate improved by 3.5% with every 1% increase in pre-hospital oxygen saturation (adjusted OR = 1.035, 95% CI: 1.005–1.066, p = 0.020) and the survival probabilities of patients who responded to voice (adjusted OR = 0.170, 95% CI: 0.050–0.579, p = 0.005), those who responded to pain (adjusted OR = 0.130, 95% CI: 0.036–0.475, p = 0.002), and those who were unresponsive (adjusted OR = 0.086, 95% CI: 0.026–0.278, p-value < 0.001) were lower than patients who were alert. Conclusion: The 30-day survival rate of patients with sepsis managed by the EMS team was 77.3%. Pre-hospital oxygen saturation and level of consciousness were associated with the survival of patients with sepsis who were managed in the pre-hospital setting.